Government Efforts to Save Micro, Small and Medium Businesses in Indonesia During the Covid-19 Pandemic - Jam'an (International Journal of Science and Society, 2020)
The government has made various efforts to save MSMEs as a result of the emergence of the Covid-19 pandemic. These efforts were carried out because of a decline in the economic sector so that if left unchecked, MSMEs could die before the pandemic ended. The research will be carried out using a qualitative approach using secondary data from various previous studies and studies. The results of the study show how other countries saved MSMEs during the pandemic. Then it was also found multiple policies that the Indonesian state has carried out to protect MSMEs from losses. Finally, several strategies, both short-term strategies and long-term strategies, can be used to save MSMEs in Indonesia.